Evidence from Turner's syndrome of an imprinted X-linked locus affecting cognitive function - Skuse, D; James, R; Bishop, D; Coppin, B; Dalton, P; Aamodt-Lepper, G; Bacarese-Hamilton, M; Cresswell, C; McGurk, R; Jacobs, P (Nature Publishing Group, 1997)
Turner's syndrome is a sporadic disorder of human females in which all or part of one X chromosome is deleted. Intelligence is usually normal but social adjustment problems are common. Here we report a study of 80 females with Turner's syndrome and a single X chromosome, in 55 of which the X was maternally derived (45,Xm) and in 25 it was of paternal origin (45,Xp). Members of the 45,Xp group were significantly better adjusted, with superior verbal and higher-order executive function skills, which mediate social interactions. Our observations suggest that there is a genetic locus for social cognition, which is imprinted and is not expressed from the maternally derived X chromosome. Neuropsychological and molecular investigations of eight females with partial deletions of the short arm of the X chromosome indicate that the putative imprinted locus escapes X-inactivation, and probably lies on Xq or close to the centromere on Xp. If expressed only from the X chromosome of paternal origin, the existence of this locus could explain why 46,XY males (whose single X chromosome is maternal) are more vulnerable to developmental disorders of language and social cognition, such as autism, than are 46,XX females.